Redox Status as a Key Driver of Healthy Pancreatic Beta-Cells - Holendová, B; Benáková, Š; Křivonosková, M; Plecitá-Hlavatá, L (Physiological research, 2024)
Redox status plays a multifaceted role in the intricate physiology and pathology of pancreatic beta-cells, the pivotal regulators of glucose homeostasis through insulin secretion. They are highly responsive to changes in metabolic cues where reactive oxygen species are part of it, all arising from nutritional intake. These molecules not only serve as crucial signaling intermediates for insulin secretion but also participate in the nuanced heterogeneity observed within the beta-cell population. A central aspect of beta-cell redox biology revolves around the localized production of hydrogen peroxide and the activity of NADPH oxidases which are tightly regulated and serve diverse physiological functions. Pancreatic beta-cells possess a remarkable array of antioxidant defense mechanisms although considered relatively modest compared to other cell types, are efficient in preserving redox balance within the cellular milieu. This intrinsic antioxidant machinery operates in concert with redox-sensitive signaling pathways, forming an elaborate redox relay system essential for beta-cell function and adaptation to changing metabolic demands. Perturbations in redox homeostasis can lead to oxidative stress exacerbating insulin secretion defect being a hallmark of type 2 diabetes. Understanding the interplay between redox signaling, oxidative stress, and beta-cell dysfunction is paramount for developing effective therapeutic strategies aimed at preserving beta-cell health and function in individuals with type 2 diabetes. Thus, unraveling the intricate complexities of beta-cell redox biology presents exciting avenues for advancing our understanding and treatment of metabolic disorders.
Keywords: homeostáza; Insulin; oxidační stres; inzulin; reaktivní formy kyslíku; signální transdukce; Homeostasis; Diabetes Mellitus, Type 2; Signal Transduction; diabetes mellitus 2. typu; oxidace-redukce; Reactive Oxygen Species; Animals; sekrece inzulinu; lidé; Humans; zvířata; beta-buňky; Insulin-Secreting Cells; Oxidation-Reduction; Oxidative Stress; Insulin Secretion